The Influence of Patient Engagement and Effective Communication on ED Image with Service Quality as a Moderating Variable - Athika Rodhya; Rokiah Kusumapradja; Wahyuni Dian (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study investigates the influence of patient involvement and effective communication on the image of the Emergency Department (ED) at Dr. Dradjat Prawiranegara Regional Hospital in Serang, with service quality acting as a moderating variable. Utilizing a quantitative research method, data were collected through questionnaires distributed to 315 patients who received emergency care services between October 1 and November 1, 2024. The data were analyzed using multiple regression analysis and Moderated Regression Analysis (MRA). The findings show that patient involvement has a significant and positive impact on the image of the ED, while effective communication alone does not show a statistically significant effect. However, service quality positively moderates the relationship between effective communication and the ED’s image, enhancing its influence. In contrast, service quality does not moderate the relationship between patient involvement and ED image. These results highlight the importance of engaging patients in medical decisions and ensuring effective communication strategies supported by high service quality to enhance the institutional image of emergency healthcare services. The study suggests that hospital management should develop integrated service improvement policies focusing on staff communication training, patient-centered care practices, and continuous quality improvement. It also recommends further qualitative studies to explore deeper insights into patient experiences and to examine other hospital departments to broaden the understanding of healthcare service quality's role in shaping hospital image.